PENGARUH PENGUNGKAPAN GREEN PRODUCT INNOVATION DAN GREEN PROCESS INNOVATION TERHADAP KINERJA PERUSAHAAN - Nurilia Perucha Sari (Universitas Negeri Surabaya, 2020)
In the current era where the economy is growing rapidly, of course it is a challenge for every company, especially in Indonesia. Given the business processes of large companies that are not environmentally friendly, air pollution and environmental pollution can have an impact on global warming. This research aims to examine whether innovations in environmentally friendly processes and products can have a good impact on the performance of an issuer in the manufacturing sector in Indonesia. Population taking in the study is that all listed companies engaged in the manufacturing industry from 2014 to 2017. After selecting the sample with a purposive sampling method, 481 samples of the observation period were obtained through audited company financial statements and listed on the Indonesia Stock Exchange. The analytical method used in this research is multiple linear regression analysis. Based on the results of the study showed that the innovation of environmentally friendly products has a positive effect on company performance, while the innovation of environmentally friendly processes alone is not able to influence the improvement of a company's performance.